2003
DOI: 10.1002/lsm.10237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Ga‐As laser irradiation on myonecrosis caused by Bothrops Moojeni snake venom

Abstract: The laser treatment significantly inhibited the ability of B. moojeni venom to rapidly disrupt the integrity of the plasma membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 18 publications
6
36
0
2
Order By: Relevance
“…The optical laser power was determined by a Newport 1835-C Multi Function Optical Power Meter® (Newport Corp., USA). Laser dose was low enough to avoid any thermal effect and chosen based on studies that had shown a beneficial effect of low-level laser therapy on the inflammatory process and myonecrotic effect (24,(27)(28)(29).…”
Section: Laser Devicementioning
confidence: 99%
“…The optical laser power was determined by a Newport 1835-C Multi Function Optical Power Meter® (Newport Corp., USA). Laser dose was low enough to avoid any thermal effect and chosen based on studies that had shown a beneficial effect of low-level laser therapy on the inflammatory process and myonecrotic effect (24,(27)(28)(29).…”
Section: Laser Devicementioning
confidence: 99%
“…The control animals were inoculated with a sterile 0.9% saline solution. and Dourado et al (10). The average wattage of the equipment was measured before the experiment with the aid of a power-measuring device (2-watt broadband power/energy meter, 13 PEM 001/J®, Melles Griot, The Netherlands).…”
Section: Venom Inoculationmentioning
confidence: 99%
“…This leads to a catalytic process involving diverse substances, giving rise to a series of inflammatory reactions (12). Due to their catalytic function, these substances can exhibit toxic or pharmacological effects such as myonecrosis, neurotoxicity and cardiotoxicity as well as hemolytic, hemorrhagic, hypotensive and anticoagulant activities and inhibition of platelet aggregation (10).…”
Section: Creatine Kinase (Ck) Activity In Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…En otros estudios morfológicos, se ha observado un efecto bioestimulatorio en el tejido fibroconectivo (Vinck et al, 2003;Shu et al, 2002y Matamala et al, 2001. En músculos de mamíferos lesionados por diversas causas, se ha reportado un aumento de tejido funcional en procesos regenerativos (Weiss & Oron, 1992;Houghton & Brown, 1999;Amaral et al, 2001;Oron et al, 2001;Dourado et al, 2003). Además, se ha observado un efecto similar en músculo esquelético de anfibios (Bibikova & Oron, 1993).…”
Section: Introductionunclassified